Mutual alteration of NOD2-associated Blau syndrome and IFNγR1 deficiency - Parackova, Zuzana; Bloomfield, Marketa; Vrabcova, Petra; Zentsova, Irena; Klocperk, Adam; Milota, Tomas; Svaton, Michael; Casanova, Jean-Laurent; Bustamante, Jacinta; Fronkova, Eva; Sediva, Anna (Journal of clinical immunology, 2020)
Blau syndrome (BS) is an auto-inflammatory granulomatous disease that possibly involves abnormal response to interferon gamma (IFNγ) due to exaggerated nucleotide-binding oligomerization domain containing 2 (NOD2) activity. Mendelian susceptibility to mycobacterial diseases (MSMD) is an infectious granulomatous disease that is caused by impaired production of or response to IFNγ. We report a mother and daughter who are both heterozygous for NOD2c.2264C˃T variant and dominant-negative IFNGR1818del4 mutation. The 17-year-old patient displayed an altered form of BS and milder form of MSMD, whereas the 44-year-old mother was completely asymptomatic. This experiment of nature supports the notion that IFNγ is an important driver of at least some BS manifestations and that elucidation of its involvement in the disease immunopathogenesis may identify novel therapeutic targets.
Keywords: Sarcoidosis; Humans; NOD2; Uveitis; Synovitis; Female; mutace; Interferon gamma Receptor; dospělí; IFNγR1; lidé; receptory interferonů; Arthritis; synovitida; IFNγ; methotrexate; sarkoidóza; signální adaptorový protein Nod2; Adult; Blau syndrome; ženské pohlaví; WES; Adolescent; artritida; Nod2 Signaling Adaptor Protein; Mutation; MSMD; uveitida; receptor interferonu gama; Receptors, Interferon; mladiství